Pondasi Perilaku Pengelolaan Keuangan Mahasiswa: Peran Dari Literasi Keuangan, Lingkungan Sosial, dan Tingkat Penghasilan Orang Tua Sebagai Pemoderasi - Febriyana, Yosita Febriyana; Yuanita, Dielanova Wynni (Jurnal Pendidikan Akuntansi (JPAK), 2024)
This research aims to analyze the influence of financial literacy and the social environment on students’ financial management behavior which is moderated by the level of parental income in Accounting study program students in the Special Region of Yogyakarta, Semarang and Salatiga. This research uses a quantitative type of research. The sample in this study was 315 respondents, taken by purposive sampling. The data collection technique was carried out using a questionnaire. The data analysis technique used is the SEM-PLS (Structural Equation Modeling) data analysis technique with SmartPLS version 4 software. Based on the research results, the following results were found: H1 is supported, students with high financial literacy have good financial management behavior. H2 is supported, students with a good social environment have good financial management behavior. H3 is not supported, parental income level moderates the influence of financial literacy on students’ financial management behavior. H4 is supported, parental income level moderates the influence of the social environment on students’ financial management behavior.